Two new species of Manerebia Staudinger from paramo habitat in the Colombian Eastern Cordillera of the Andes (Lepidoptera: Nymphalidae, Satyrinae, Pronophilina) - Mahecha-J., Oscar; Triviño, Paola; Andrade-C, M. Gonzalo; Pyrcz, Tomasz W. (Zootaxa, 2021)
Two new species of the genus Manerebia Staudinger, 1897 (Nymphalidae, Satyrinae) are described from paramo habitat on the eastern slopes of the Colombian Eastern Cordillera in the area of Pisba and La Colorada: Manerebia bernito n. sp. and Manerebia clarita n. sp. Both are morphologically most similar to Manerebia levana and Manerebia pervaga, and the possible phylogenetic relationship between them is hypothesized. Their habitat is described and a proposal of their conservation status is made. With the addition of the two new species described in this study, a total of 15 species of Manerebia are reported from Colombia. However, a molecular analysis should be carried out to validate the taxonomic status of several species of Manerebia, in particular having in mind a potentially high cryptic diversity of this genus.